A Bibliometric Analysis of the Role of Companies in Achieving the Sustainable Development Goals - Judijanto, Loso; Muhtadi, Muhamad Ammar; Nurhasanah, Dila Padila (Westscience Press, 2024)
The pursuit of Sustainable Development Goals (SDGs) has become paramount in addressing global environmental, social, and economic challenges. In this context, the role of companies in advancing sustainable development has garnered increasing attention. This research conducts a comprehensive bibliometric analysis to elucidate the landscape of research pertaining to the involvement of companies in achieving the SDGs. By systematically analyzing scholarly literature spanning from 1992 to 2024, encompassing 980 papers and 162,376 citations, key themes, trends, and gaps in the literature are uncovered. The analysis reveals a robust citation impact, with an average of 5,074.25 citations per year and 165.69 citations per paper. Notably, the study identifies prominent works such as the World Health Organization's